The Learning Curve: Trends in the First 100 Immediate Lymphatic Reconstructions Performed at a Single Institution. Issue 5 (June 2021) - Le, Nicole K.; Weinstein, Brielle; Serraneau, Karisa; Tavares, Tina; Laronga, Christine; Panetta, Nicholas
Abstract : Background: Cancer-related lymphedema will affect 10% to 50% of breast cancer survivors. Early data show that immediate lymphatic reconstruction may help prevent breast cancer lymphedema; however, the details have not been fully elucidated. The purpose of this study was to evaluate the cohort of our first 100 patients for trends in demographics, treatment, and technique. Methods: At a tertiary care cancer center, high-risk breast cancer–related lymphedema patients underwent axillary reverse lymphatic mapping and immediate lymphatic reconstruction. After institutional review board approval, demographics, technique, and outcomes were recorded. The first 100 patients were analyzed to compare the differences between the first 50 versus the second 50 patient cohorts. Results: Of the first 100 axillary reverse lymphatic mapping performed, there was a significant difference in neoadjuvant chemotherapy with 81% in the earlier cohort versus 98% in the later cohort ( P = 0.01). An arborized technique was used more frequently in the second cohort (82% vs 54%, P = 0.01). The incidence of lymphedema was lower in the latter cohort (7 patients vs 1 patient, P = 0.03). The first cohort was 12.2 times more likely to develop lymphedema despite lymphatic reconstruction than the second cohort ( P = 0.03). Conclusions: The data demonstrate multiple trends in the learning curve associated with immediate lymphatic reconstruction at a single institution including improvements in identifying and dissecting lymphatic structures, performing more anastomoses per patient, using the arborized technique more frequently, performing the operation with shorter operative times, and reducing the incidence of lymphedema.